Effects of an antimicrobial peptide on transport- and novel environment-induced stress in British Shorthair cats - Chen, Shaohao; Zhang, Miaomiao; Yan, Haoran; Ye, Lan; Xue, Qishan; Wu, Yuansheng; Zhao, Kun; Jiang, Yizhou; Wang, Qingxin; Zhu, Jiang; Guo, Yan; Liu, Qingshen; et al. (Frontiers in Veterinary Science, 2026)
Antimicrobial peptides (AMPs) are natural short peptides with known immunomodulatory and anti-inflammatory properties. Their application in feline stress management have not been widely studied. This study aimed to evaluate the effects of dietary AMPs derived from Saccharomyces cerevisiae on cats exposed to transportation and novel environment. Twelve cats were randomly allocated to a control group or a group fed with AMPs. After pre-feeding for 2 weeks, all cats underwent a two-hour transportation and were subsequently housed individually in novel environment for 1 week. Behavioral observations, biochemical assays, gut microbiota analysis, transcriptomics, and metabolomics were performed. AMPs supplementation significantly increased nighttime sleep duration, reduced activity on transportation day, and lowered cat stress scores (CSS) during the first 3 days in the novel environment. In the open field test (OFT), AMPs reduced escape and pacing behaviors (p < 0.05). AMPs also significantly decreased serum levels of CRH, COR, SAA, IL-1β, and IL-6, while increasing IgG and Apo-A1 after recovery. Antioxidant capacity was also significantly improved by AMPs, as shown by the elevated GSH-Px and reduced MDA. Higher abundances of Bacteroides, Prevotella, and Collinsella (p < 0.05), and lower Schaalia (p < 0.05) were observed in the AMP group. Metabolomics revealed that AMPs primarily regulated the nutritional status and immune function of cats by affecting amino acid and lipid metabolism, thereby enhancing their stress resilience. Transcriptomic analysis indicated that AMPs significantly upregulated pathways related to immune function, cell signal transduction, inflammatory response, and lipid metabolism, while downregulating those associated with viral processes. Dietary supplementation of AMPs alleviates stress in cats, potentially by reducing inflammatory and oxidative stress, and modulating gut microbiota, as well as metabolic and immune pathways.